DETERMINAN YANG MEMPENGARUHI KINERJA DOSEN DALAM PELAKSANAAN TRI DHARMA PERGURUAN TINGGI - Lilis Setyowati (P3M STIEM BONGAYA, 2020)
This study aims to identify the factors that influence the increase in the performance of lecturers in implementing the tri dharma of higher education. The sampling method uses purposive sampling technique and analysis techniques using multiple linear regression tests. The research was conducted at one of the private universities in Semarang with a total sample of 63 respondents. The results showed that the increase in lecturer performance was influenced by professional competence and commitment to the profession, while leadership motivation, training, educator certification, and organizational culture did not affect the improvement of lecturers' performance in implementing the tri dharma of higher education.